Who Should Regulate The Industry of Financial Technology? - Suwinto Johan; Sugiarto Sugiarto (Pandecta Research Law Journal, 2022)
Financial technology (fintech) has outgrown its capacity. Industry supervision and consumer protection have become a challenge. Until now, the Indonesian Financial Services Authority (OJK) has been considered responsible for supervising the financial technology industry. The purpose of this research is to determine whether the Indonesian Financial Services Authority is capable of leading the fintech industry and whether a separate agency to oversee the fintech industry is necessary. This study employs a normative juridical methodology. This study examines the entire financial industry. According to this research, the Indonesian Financial Services Authority lacks the authority to regulate the fintech industry. The government should enact special legislation and regulations to govern the fintech industry. The regulator must consider creating a separate agency to supervise the fintech industry, similar to the Indonesian Financial Services Authority. This particular agency is comprised of individuals with ties to the financial sector, the telecommunications industry, and other law enforcement personnel.